(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
This study aimed to highlight the impact of e-government development indicators on enhancing financial inclusion. This was achieved through the examination of the independent variable (e-government) represented by three dimensions: the Online Service Index (OSI), Telecommunications Infrastructure Index (TII), and Human Capital Index (HCI). The study also investigated their influence on the dependent variable (financial inclusion) represented by two dimensions: the growth rate of commercial bank branches (GrCBB) and the growth rate of ATMs (GrATMs) during the period from 2005 to 2022. The study employed a descriptive-analytical methodology to achieve its objectives. To test the hypotheses, the Autoregressive Distributed Lag (ARDL) model for cointegration was utilized, using the statistical software Eviews 10.The results of the statistical analysis and hypothesis testing revealed a statistically significant positive impact of both the Telecommunications Infrastructure Index and the Human Capital Index on the growth rate of commercial bank branches. However, there was no significant impact of the Online Service Index throughout the study period. Additionally, there was a statistically significant positive impact of both the Telecommunications Infrastructure Index and the Human Capital Index on the growth rate of ATMs. On the other hand, there was a statistically significant negative impact of the Online Service Index on the growth rate of ATMs during the studied period.The study recommends the need to encourage the use of online services, promote private companies to develop innovative digital financial applications and services, and facilitate partnerships between the government and technology companies to enhance technological development.